O psícologo empírico como Linneu da psique: apontamentos sobre a crítica hegeliana à psicologia empírica (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: In this paper, I inquire into Hegel’s criticism of empirical psychology and the model of mind the discipline puts forth. In order to do so, I underscore the connections between what Hegel considers the methodology of empirical psychology and the methodology he sees at work in the taxonomy of Carl Linnaeus. The paper proceeds as follows: (1) I first survey Hegel’s position on empirical psychology, then (2) focus on the method that Hegel attributes to the discipline. (3) I locate this critique within the larger scope of Hegel’s criticism of “observation” as a scientific method; in particular, I focus on Hegel’s criticism of Linnaeus’ taxonomy. (4) I show the parallels between Hegel’s accounts of the two domains, using his remarks on Linnaeus to shed light on empirical psychology. (5) Finally, I offer some concluding remarks on the peculiar role played by the notion of Gedächtnis within this context.